A Study of Soluble-Powdered Natural Dyes - Ngo, June Siok Kheng; Ong, W.F.; Ahmad, F.B.; Bujang, K.B. (Emerald Group Publishing Limited, 2013)
This paper highlights an on-going study that produces soluble-powdered natural dye extracts from Sebangki barks (Neesia spp., Bomb.; Tristaniopsis spp., Myrt.), Engkerabai Paya leaves (Psychotria viridiflora Zoll. ex. Miq.) and Engkudu roots (Morinda citrifolia L.). These three natural colourants are typically used by the native Iban community in Sarawak to dye silk threads for Pua Kumbu weaving. The two primary objectives of this study are to convert natural dye extracts into soluble powder using solvent extraction and to formulate textile dyeing recipes with good colourfastness and lightfastness using powdered natural dyes extracts. The successful experiments show that distilled water and ethanol can be used as solvents to extract natural dyes from Neesia spp., Bomb.; Tristaniopsis spp., Myrt. barks, Morinda citrifolia L. roots, Psychotria viridiflora Zoll. ex. Miq. leaves. In addition, it is proven that the method of freeze drying is capable of converting liquid dye extracts into soluble powder.